ISSUE OF INSURGENCY IN ASSAM AND ITS REFLECTION IN CONTEMPORARY ASSAMESE LITERATURE (CAHIERS MAGELLANES-NS, 2024)
Insurgency and violence are not an alien topic in the context of North East India in general and Assam in particular. Right after India's independence, the flame of insurgency started to engulf then Naga Hills district (now Nagaland state) of then undivided Assam. Manipur, Mizoram, Tripura and Nagaland all had severe insurgency problems right from 1950's and 1960's. Finally, a formal insurgent group called ULFA (United Liberation Front of Assam), formally took shape in 1979 in upper Assam with overt and covert support of other insurgent groups in neighboring states. The perceived perception of alienation and exploitation in the minds of a group of handful misguided youths kept Assam burning for next 30 years and sporadic incidents are still continuing as not all members of the banned insurgent group have given up the path of violence till now. Naturally literary work in Assam too started reflecting a diverse set of views during this turbulent period. Some literary works were protagonists, some were antagonists to the insurgents.  Yet some other literary works were totally neutral that depicted the travails and sufferings of common people both in the hands of insurgents and security forces. It was the perfect cauldron of grief, sorrow, fear and revenge. Numerous writers paid the price for being bold with their pen, both in the hands of insurgents and occasionally in the hands of law enforcement auttlhorities. Finally, a powerful mediator group headed by noted literary personalities in Assam was tasked by both sides to broker peace.  This mediator group, with the presence and clout of several noted literary personalities of the state, finally succeeded in persuading a sizeable section of insurgents yo shun the mindless path of violence and resolve their grievances through dialogue and peaceful means.  This broadly sums up the influence of literature in a very turbulent period of Assam.